Update in Glaucoma Medicinal Chemistry: Emerging Evidence for the Importance of Melatonin Analogues - Crooke, A.; Colligris, B.; Pintor, J. (Current Medicinal Chemistry, 2012)
Glaucoma is a chronic progressive optic neuropathy, which can result in visual impairment and blindness. Elevated intraocular pressure (IOP) is currently the only modifiable risk factor. Several recent studies have shown the benefits of IOP reduction in open-angle glaucoma. Therefore, current glaucoma drugs are IOP-lowering substances such as α2-adrenergic agonists, β2-adrenergic antagonists, carbonic anhydrase inhibitors and hypotensive lipids, which are used separately or in combination. In spite of the wide variety of antiglaucoma medicines, all therapies have several undesirable side effects. As a consequence, there are constant research attempts on the discovery of novel ocular hypotensive drugs. In the current paper, we review the latest available patents and literature for the pharmacological treatment of glaucoma, focusing on their molecular targets and/or their chemical characteristics and especially directed to melatoninergic drugs. Melatonin is a hormone secreted into the blood mainly from the pineal gland allowing the entrainment of the circadian rhythms of several biological functions. Melatonin and its analogues potently reduce IOP in rabbits, monkeys and humans. In addition, there are indications of long-term hypotensive effects and a proven neuroprotective role of melatoninergic substances. Furthermore, antidepressant and normalizing circadian rhythm actions of melatonin analogues might be beneficial for glaucoma patients. All the above mentioned facts suggest these agents as proper candidates for the glaucoma treatment. Consequently, the scientific research has given new and significant progress on the development of new, potent and selective melatonin ligands.
Keywords: Glaucoma